2001
DOI: 10.1161/hc4701.099578
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptor Blockers Restore Cardiac Calcium Release Channel (Ryanodine Receptor) Structure and Function in Heart Failure

Abstract: Background-␤-Adrenergic receptor blockade is one of the most effective treatments for heart failure, a leading cause of mortality worldwide. The use of ␤-adrenergic receptor blockers in patients with heart failure is counterintuitive, however, because they are known to decrease contractility in normal hearts. The ryanodine receptor (RyR2) on cardiac sarcoplasmic reticulum is the key calcium release channel required for excitation-contraction coupling. In failing hearts, the stoichiometry and function of the Ry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
106
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 53 publications
9
106
0
2
Order By: Relevance
“…Thus, the present studies not only provide a basis for treating exercise-induced cardiac arrhythmias that cause SCD but also indicate that JTV519 could be beneficial in the treatment of heart failure, which is associated with aberrant SR Ca 2ϩ leak via calstabin2-depleted RyR2 channels. 9,33 Furthermore, these studies confirm results with a high-affinity calstabin2-D37S mutant that normalized the channel function of constitutively PKA-phosphorylated RyR2 channels. 12 In summary, genotype-phenotype studies in RyR2 mutation carriers showed high mortality rates and a reproducible threshold heart rate above which ventricular arrhythmias occur.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, the present studies not only provide a basis for treating exercise-induced cardiac arrhythmias that cause SCD but also indicate that JTV519 could be beneficial in the treatment of heart failure, which is associated with aberrant SR Ca 2ϩ leak via calstabin2-depleted RyR2 channels. 9,33 Furthermore, these studies confirm results with a high-affinity calstabin2-D37S mutant that normalized the channel function of constitutively PKA-phosphorylated RyR2 channels. 12 In summary, genotype-phenotype studies in RyR2 mutation carriers showed high mortality rates and a reproducible threshold heart rate above which ventricular arrhythmias occur.…”
Section: Discussionsupporting
confidence: 77%
“…31,32 Treatment with ␤-adrenergic receptor blockers reverses PKA hyperphosphorylation and calstabin2 depletion in heart failure, and the beneficial effects of ␤-blocker treatment in patients with exercise-induced arrhythmias may be related to prevention of RyR2-mediated SR Ca 2ϩ leak. 33 Recently it was reported that the 1,4-benzothiazepine derivative JTV519 inhibits FK506-induced intracellular Ca 2ϩ leak in the heart and may normalize leaky RyR2 in failing hearts. 13,15 Treatment of phosphorylated RyR2-P2328S channels with 1.0 mol/L JTV519 completely normalized the gain-of-function defect, and the significant leftward shift of Ca 2ϩ sensitivity was rescued ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…2 We previously reported that in a dog model of pacinginduced heart failure, a prominent abnormal Ca 2ϩ leak occurs through the RyR owing to a partial loss of RyR-bound FKBP12.6. 3 ␤-Adrenergic receptor blockade has been shown to correct the defective interaction of FKBP12.6 with RyR 4,5 that is triggered by the protein kinase A (PKA)-mediated hyperphosphorylation of RyR. 6 Indeed, this correction leads to a restoration of the stoichiometry of the RyR2 macromolecular complex, 4 a normalization of the single-channel function of RyR, 4 and a prevention of the Ca 2ϩ leak from RyR.…”
mentioning
confidence: 99%
“…3 ␤-Adrenergic receptor blockade has been shown to correct the defective interaction of FKBP12.6 with RyR 4,5 that is triggered by the protein kinase A (PKA)-mediated hyperphosphorylation of RyR. 6 Indeed, this correction leads to a restoration of the stoichiometry of the RyR2 macromolecular complex, 4 a normalization of the single-channel function of RyR, 4 and a prevention of the Ca 2ϩ leak from RyR. 5 Recently, we found that a new cardioprotective agent, JTV519, corrects the defective FKBP12.6-mediated stabilization of RyR, leading to an improvement in cardiac function during the development of heart failure.…”
mentioning
confidence: 99%
“…It remains to be seen to what extend the beneficial aspects of JTV519 and future derivatives rely on the direct actions of FKBP rebinding to RyR and thus a novel mechanism. In addition, it is not known whether bringing back FKBP could really add benefit on-top of existing pharmacological interventions: Marks' group has shown that ␤-adrenergic blockade, a clinically well proven strategy to treat heart failure and arrhythmia, could already completely normalize the stochiometry of the RyR multi-protein complex with respect to the five proteins mentioned above and reverted the increased open probability of isolated channels (40). Likewise, low-dose propranolol treatment completely prevented SR Ca leak in a dog model of heart failure and conformational changes in RyR as well as RyR-FKBP12.6 stochiometry (9), questioning potential on-top benefits of strategies to restore FKBP12.6-RyR binding.…”
Section: Calcium In Cardiac Excitationcontraction Couplingmentioning
confidence: 99%